2011
DOI: 10.3346/jkms.2011.26.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Type D Personality Construct in the Korean Population: A Validation Study of the Korean DS14

Abstract: This study aimed to develop a Korean version of the Type D Personality Scale-14 (DS14) and evaluate the psychiatric symptomatology of Korean cardiac patients with Type D personality. Healthy control (n = 954), patients with a coronary heart disease (n = 111) and patients with hypertension and no heart disease (n = 292) were recruited. All three groups completed DS14, the Eysenck Personality Questionnaire (EPQ), the state subscale of Spielberger State and Trait Anxiety Inventory (STAI-S), the Center for Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
87
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 26 publications
9
87
2
3
Order By: Relevance
“…The reliability estimates that we observed for the retest reliabilities of SI and NA scores over a time period of 6 years were lower than those reported for shorter time periods [2,[4][5][6][7][8] and corresponded to the values reported for a sample of patients assessed before and 6 months after cardiac surgery [9]. Following Shrout [31], who proposed that reliability coefficients between .41 and .60 be labeled as fair and coefficients between .61 and .80 as moderate, the sizes of the reliability coefficients can be classified as fair to moderate.…”
Section: Relative Stabilitycontrasting
confidence: 82%
See 3 more Smart Citations
“…The reliability estimates that we observed for the retest reliabilities of SI and NA scores over a time period of 6 years were lower than those reported for shorter time periods [2,[4][5][6][7][8] and corresponded to the values reported for a sample of patients assessed before and 6 months after cardiac surgery [9]. Following Shrout [31], who proposed that reliability coefficients between .41 and .60 be labeled as fair and coefficients between .61 and .80 as moderate, the sizes of the reliability coefficients can be classified as fair to moderate.…”
Section: Relative Stabilitycontrasting
confidence: 82%
“…Other studies that observed no change in NA and SI scores over time [4,6,8,9] Notes. a -d = (mean at t2-mean at t1)/pooled standard deviation; b -age dichotomized at the median; all r's p b .001; * p b .05; ** p b .01; *** p b .001.…”
Section: Absolute Stabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…The validity and reliability of the DS_14 has been established in various countries, among patients with cardiac diseases (7)(8)(9)(10)(11) and chronic pain (12), and healthy individuals (13).…”
Section: Introductionmentioning
confidence: 99%